Web-Based Guest Lecture Information System for Committee and Student Users at FMIPA UNSRAT - Andrea Emailly Sumakul; Chriestie Ellyane Juliet Clara Montolalu; Mahardika Inra Takaendengan; Benny Pinontoan; Wisard Widsli Kalengkongan; Dodisutarma Lapihu (Universitas Teknokrat Indonesia, 2026)
Guest lecture management at FMIPA UNSRAT currently suffers from significant fragmentation across WhatsApp, Google Forms, and paper attendance, leading to data duplication, information inconsistencies, and administrative inefficiency. This condition hinders effective decision-making and stakeholder engagement. This study aims to design and develop a centralized Web-Based Guest Lecture Information System to integrate the entire event lifecycle, including publication, registration, digital attendance, and reporting. The system was developed using the Waterfall model with Laravel framework and MySQL database. Comprehensive evaluation involved Black Box Testing, User Acceptance Testing (UAT) with committee members, and User Perception Testing with students. Results indicate a 100% success rate in Black Box Testing across 42 functional scenarios. UAT yielded a 90.4% acceptance rate among committee members, validating operational feasibility and workflow alignment. Furthermore, User Perception Testing achieved a 91.04% satisfaction score among students, with Behavioral Intention reaching 93.6%. These findings demonstrate that the system significantly reduces data fragmentation and improves administrative efficiency compared to manual processes. The system is deemed feasible for immediate deployment, offering a robust solution for centralized academic event management. However, limitations exist regarding financial module integration. Future work should focus on API integration with the central university portal and automated honorarium processing to further enhance scalability and institutional adoption.